Co-precipitation technique to prepare BaTa2O6 - Navale, S. C.; Samuel, Violet; Gaikwad, A. B.; Ravi, V. (Ceramics International, 2007)
A mixture of ammonium oxalate and ammonium hydroxide was used to co-precipitate barium and tantalum ions as barium oxalate and tantalum hydroxide under basic conditions. On calcination at 750 degrees C, this precursor yielded BaTa2O6 (BT) ceramics. This is much lower temperature as compared to that prepared by traditional solid-state method (1000 degrees C) as reported for the formation of BaTa206. Transmission electron microscope (TEM) investigations revealed that the average particle size is 70 nm for the calcined powders. The room temperature dielectric constant at 1 kHz is found to be 100. (c) 2005 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: barium tantalate; Ceramics; Electron microscopy; Oxides; X-ray diffraction

Influence of preparation method on activity and stability of Ni catalysts supported on Gd doped ceria in dry reforming of methane - Gurav, Hanmant R.; Dama, Srikanth; Samuel, Violet; Chilukuri, Satyanarayana (Journal of CO2 Utilization, 2017)
Nickel catalysts supported on Gd doped ceria (NGDC), with various Ni content, were prepared through different preparation routes and evaluated for dry reforming of methane (DRM). Their detailed characterization revealed that method of preparation plays an important role in Ni dispersion, with catalysts prepared through co-precipitation showing high Ni dispersion. The co-precipitated 12NGDC-cp catalyst with 12 wt% NiO was found to be superior in terms of high CO2 and CH4 conversions compared to catalysts prepared through citrate gel or impregnation methods Even H-2 and CO yields are high on this catalyst, while it shows excellent durability with stable activity even after 100 h on-stream. Thermogravimetric analysis of spent catalyst showed presence of coke, with transmission electron microscopic studies pointing to the presence of Ni crystallites at the mouth of the carbon whiskers. These Ni crystallites appear to be still active for DRM reaction. Among the spent catalysts, the carbon formation was high on catalysts that have bigger Ni crystallites, with the catalysts prepared through impregnation and citrate gel methods having higher coke. Investigations also reveal that the conversion of active (amorphous) carbon into stable (graphitic) carbon depends on the Ni crystallite size, temperature and duration of the reaction. These studies demonstrate that Gd doped ceria is a good support for Ni, to obtain high DRM activity and very good on-stream stability provided the catalysts are prepared through an appropriate method.